2008
DOI: 10.1111/j.1945-5100.2008.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Frontier Mountain meteorite specimens of the acapulcoite‐lodranite clan: Petrography, pairing, and parent‐rock lithology of an unusual intrusive rock

Abstract: Abstract-In this paper we reconstruct the heterogeneous lithology of an unusual intrusive rock from the acapulcoite-lodranite (AL) parent asteroid on the basis of the petrographic analysis of 5 small (<8.3 g) meteorite specimens from the Frontier Mountain ice field (Antarctica). Although these individual specimens may not be representative of the parent-rock lithology due to their relatively large grain size, by putting together evidence from various thin sections and literature data we conclude that Frontier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Brachinites: Nehru et al (1983); Smith et al (1983); Warren and Kallemeyn (1989); Mittlefehldt et al (2003); Swindle et al (1998); Kring et al (1991); Wlotzka (1993b); Grossman (1998); Connolly et al (2006, 2008). Acapulcoites: McCoy et al (1996); Patzer et al (2004); Burroni and Folco (2008); Yugami et al (1998). Lodranites: Takeda et al (1994); Papike et al (1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachinites: Nehru et al (1983); Smith et al (1983); Warren and Kallemeyn (1989); Mittlefehldt et al (2003); Swindle et al (1998); Kring et al (1991); Wlotzka (1993b); Grossman (1998); Connolly et al (2006, 2008). Acapulcoites: McCoy et al (1996); Patzer et al (2004); Burroni and Folco (2008); Yugami et al (1998). Lodranites: Takeda et al (1994); Papike et al (1995).…”
Section: Resultsmentioning
confidence: 99%
“…2. Acapulcoites: Mittlefehldt et al (1996); Mittlefehldt et al (1998) and references therein; Burroni and Folco (2008). Lodranites: Takeda et al (1994), Nagahara and Ozawa (1986); Nagahara (1992); McCoy et al (1997); Mittlefehldt et al (1998) and references therein.…”
Section: Resultsmentioning
confidence: 99%
“…(obtained on several specimens of the same meteorite) and the median of specimen mass are also indicated. The same data for selected chondrite groups (after Rochette et al 2003 and2008) is indicated, as well as for examples of terrestrial extrusive rocks (basaltic and rhyolitic flow from the Ethiopian traps after Rochette et al 1999) and intrusive rocks (granites from Corsica and Sardinia after Gattacceca et al 2004). In the terrestrial case, N is the number of sites (flow or outcrop), each one consisting of 3 to 9 specimen of about 10 cm 3 each.…”
Section: Ungrouped Achondritesmentioning
confidence: 89%
“…Typically, the s.d. for a given chondrite is less than 0.1 (on average 0.07 see Rochette et al 2003 and2008). Larger s.d.…”
Section: Measurement and Database Constructionmentioning
confidence: 93%
See 1 more Smart Citation